2018
DOI: 10.1097/jcn.0000000000000488
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the 5-Item Medication Adherence Report Scale in Older Stroke Patients in Iran

Abstract: Background: There is a lack of feasible and validated measures to self-assess medication adherence for older patients with stroke. In addition, the potential determinants of medication adherence for older patients with stroke remain unclear. Objectives: The aims of this study were to (1) examine the psychometric properties of a 5-item questionnaire on medication adherence, specifically the 5-item Medication Adherence Report Scale (MARS-5), and (2) explore the determinants of medication adherence. Methods: Stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 42 publications
0
44
2
4
Order By: Relevance
“…The MARS scale has been shown to correlate well with other indirect methods, including pill counts among patients with hypertension and refill rates (using medication possession ratio) among patients with stroke. 43,44 Furthermore, the subtype analyses sometimes included small numbers leading to wide confidence intervals and loss of power. Due to the cross-sectional design, no causal inferences can be made regarding the temporal association between medication beliefs and non-adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The MARS scale has been shown to correlate well with other indirect methods, including pill counts among patients with hypertension and refill rates (using medication possession ratio) among patients with stroke. 43,44 Furthermore, the subtype analyses sometimes included small numbers leading to wide confidence intervals and loss of power. Due to the cross-sectional design, no causal inferences can be made regarding the temporal association between medication beliefs and non-adherence.…”
Section: Discussionmentioning
confidence: 99%
“…An explanation for these inconsistent results could be the use of pharmacy refill data as reference standard, since this measures another underlying construct compared to self-reported questionnaires. However, a large number of studies have shown acceptable validity and reliability of MARS-5 and therefore we have chosen this measure for this study ( Cohen et al, 2009 ; Mora et al, 2011 ; Bäck et al, 2012 ; Salt et al, 2012 ; Horne, 2013 ; Lin et al, 2018 ). The chosen cut-off value for MARS-5 might be a plausible explanation for the absence of effects.…”
Section: Discussionmentioning
confidence: 99%
“…The MARS-5 sum score was also dichotomized, where a score below 25 points indicates non-adherence. The MARS-5 questionnaire is an easy-to-use tool and shows acceptable reliability and validity ( Horne et al, 2001 ; Cohen et al, 2009 ; Mora et al, 2011 ; Bäck et al, 2012 ; Salt et al, 2012 ; Horne, 2013 ; Lin et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Differential item functioning (DIF) was further computed in the Rasch model to test the measurement invariance of the SABAS across subgroups at the item level. More specifically, if the subgroup is gender, DIF can clearly identify which item content for males as compared with females are easier or harder to achieve (Lin et al 2018b, c). The suggested cutoff of DIF is < 0.5 in the DIF contrast (i.e., the difference of difficulty between two subgroups) (Lin et al 2018b, c).…”
Section: Psychometric Testing Using Rasch Analysismentioning
confidence: 99%